Empathetic Practice: The Struggle and Virtue of Empathizing with a Patient's Suffering. Issue 2 (18th April 2019) - Campelia, Georgina; Tate, Tyler
Abstract: In this article, our analysis of empathy in the clinical context hinges on the complexities of patients who are acutely suffering. Using a case concerning a heart transplant patient with Duchenne muscular dystrophy, Alex, and his nurse, Joe, we investigate how empathy's phenomenological nebulousness can generate doubts about its virtue. Even when asking, "How are you, Alex?" Joe hates the question; it seems empty, silly. Cases like this show both that the enactment of empathy is sometimes challenging and that it can be reasonable to wonder if empathy is a virtue at all. Perhaps Alex's suffering is simply too massive: Joe cannot possibly know how he feels, so why try? Perhaps empathy would only cause Joe to suffer along with Alex. Not only is empathy difficult to produce in the context of Alex's suffering; it may not even be possible; and if we simply cannot muster empathy, what is the point of morally demanding it? In response, we distinguish different kinds of empathic engagements from one another and offer separate counsel. We argue that it is important to understand empathy as something that must be honed across varied contexts before it can be called a virtue. Conceptualizing and operationalizing empathy in this way helps to ground its possibility and virtue even in the most challenging and complex clinical encounters.